THE ROLE OF FARMER AND DEHKAN FARMS IN THE AGRARIAN DEVELOPMENT OF THE FERGANA REGION - Maroziqov , Akmal (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the processes of formation and development of farmer and dehkan farms in the Fergana region, their role in the agrarian economy, and their impact on production efficiency. It also highlights the strengthening of property relations, structural changes in agriculture, the emergence of new forms of entrepreneurship, and their contribution to ensuring food security.